Maximum Power Point Tracking (MPPT) Based Particle Swarm Optimization (PSO) for hydrokinetic energy harnessing - Wan Ismail, Ibrahim; Mohd Rusllim, Mohamed; Raja Mohd Taufika, Raja Ismail; Mohd Riduwan, Ghazali; Ping, C. L. X. (Springer, 2024)
This paper presents a design and modeling of the Particle Swarm Optimization (PSO)-based maximum power point tracking (MPPT) algorithm specifically tailored for variable-speed fixed-pitch vertical axis hydrokinetic turbines. The proposed algorithm can maximize electrical power without requiring additional sensors and prior knowledge of the water turbine characteristics. Unlike the conventional MPPT algorithm, the PSO-based MPPT algorithm exhibits minimal oscillations at the maximum power once the true peak is located. The PSO MPPT algorithm is characterized by its simplicity, flexibility, accuracy, and efficiency in tracking the maximum power under different water velocities. The simulation results by MATLAB/Simulink indicated that the PSO MPPT can achieve 83% efficiency in terms of output power and reduce the oscillation during dynamic steady-state.